VIABILITY OF THE PROBIOTIC MICROORGANISMS Lactobacillus casei 01, Lactobacillus acidophilus La-5, Bifidobacterium BB12 DURING COTTAGE CHEESE SHELF LIFE - OBANDO C., Mónica; BRITO C., Carmen S.; SCHÖBITZ T., Renate P.; BAEZ M., Liliana A.; HORZELLA R., Mariela Y. (Vitae, 2010)
The objective of this research was to evaluate the viability of three microorganisms considered as probiotics: Lactobacillus casei 01, Bifidobacterium BB12 and Lactobacillus acidophilus La-5, during cottage cheese shelflife (0, 7, 14, and 7 days thereafter equivalent to 21 days), and the influence on sensory characteristics of the products. The study was carried in four treatments and three replications. Control treatment (T1) without probiotics; treatment T2 containing Lb. casei 01; treatment T3 containing Lb. acidophilus La-5; and treatment 4, with the addition of Bifidobacterium BB12. The cream with the addition of probiotics was added to the cheese which is stored at 4ºC. The viability evaluation of microorganisms was carried through microbiology analysis and its quality characteristics obtained through physical, chemical and sensory analyses of the products at 0, 7 and 14 days. Bifidobacterium had higher counts than 1 x 106 ufc/g up to the end to the shelflife (14 days) and treatments with Lb. acidophilus and Lb. casei presented higher counts than 1 x 106 ufc/g up to 21 storage days. However, Lb. casei presented a greater viability loss through the time. Physicochemical and microbiology quality were normal and there were no significant differences between treatments(P>0.05). The sensory quality is in a way affected by the addition of microorganisms, while sensory attributes like flavour and grain firmness does not present significant differences, but aroma and humidity sensation does present significant differences between treatments (P<0.05).